Effect of ozone gas on the shear bond strength to enamel - Patricia Teixeira Pires; Joao Cardoso Ferreira; Sofia Arantes Oliveira; Mario Jorge Silva; Paulo Ribeiro Melo (University of São Paulo, 2013)
Ozone is an important disinfecting agent, however its influence on enamel adhesion has not yet been clarified. Objective: Evaluate the influence of ozone pretreatment on the shear strength of an etch-and-rinse and a self-etch system to enamel and analyze the respective failure modes. Material and Methods: Sixty sound bovine incisors were used. Specimens were randomly assigned to four experimental groups (n=15): Group G1 (Excite® with ozone) and group G3 (AdheSE® with ozone) were prepared with ozone gas from the HealOzone unit (Kavo®) for 20 s prior to adhesion, and groups G2 (Excite®) and G4 (AdheSE®) were used as control. Teeth were bisected and polished to simulate a smear layer just before the application of the adhesive systems. The adhesives were applied according to the manufacturer's instructions to a standardized 3 mm diameter surface, and a composite (Synergy D6, Coltene Whaledent) cylinder with 2 mm increments was build. Specimens were stored in 100% humidity for 24 h at 37°C and then subjected to a thermal cycling regimen of 500 cycles. Shear bond tests were performed with a Watanabe device in a universal testing machine at 5 mm/min. The failure mode was analyzed under scanning electron microscope. Means and standard deviation of shear bond strength (SBS) were calculated and difference between the groups was analyzed using ANOVA, Kolmogorov-Smirnov, Levene and Bonferroni. Chi-squared statistical tests were used to evaluate the failure modes. Results: Mean bond strength values and failure modes were as follows: G1- 26.85±6.18 MPa (33.3% of adhesive cohesive failure); G2 - 27.95±5.58 MPa (53.8% of adhesive failures between enamel and adhesive); G3 - 15.0±3.84 MPa (77.8% of adhesive failures between enamel and adhesive) and G4 - 13.1±3.68 MPa (36.4% of adhesive failures between enamel and adhesive). Conclusions: Shear bond strength values of both adhesives tested on enamel were not influenced by the previous application of ozone gas.